2018
DOI: 10.1016/j.radcr.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous adrenal vein anatomy complicating the evaluation of primary hyperaldosteronism

Abstract: Adrenal vein development in utero occurs concurrently with the development of the inferior vena cava, the renal veins, and the gonadal veins. The embryologic formation of these veins involves communication of various venous systems. Although the left adrenal-renal vein complex is most commonly described as a shared emptying of the left adrenal vein and the left inferior phrenic vein into the left renal vein, there have been reports of numerous anatomic variations of this complex. In this report, we present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Similarly, variants of venous anatomy can complicate AVS during the evaluation of PA. Fujii et al reported a case where AVS was performed in a patient with PA and a left IVC whose left adrenal vein drained directly into the IVC 9. Ford et al presented a case of a rare variant of the left adrenal vein, in which the left gonadal vein drained into the left adrenal vein after taking an atypical course superolateral to the left kidney 10. This anatomical variant also occurred in the context of a patient with PA and complicated AVS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, variants of venous anatomy can complicate AVS during the evaluation of PA. Fujii et al reported a case where AVS was performed in a patient with PA and a left IVC whose left adrenal vein drained directly into the IVC 9. Ford et al presented a case of a rare variant of the left adrenal vein, in which the left gonadal vein drained into the left adrenal vein after taking an atypical course superolateral to the left kidney 10. This anatomical variant also occurred in the context of a patient with PA and complicated AVS.…”
Section: Discussionmentioning
confidence: 99%
“…From its origin in the adrenal hilum, it typically travels inferomedially to form a common trunk with the inferior phrenic vein and then drain into the left renal vein. 7,19 Variations occur in less than 10% of patients and most commonly includes duplication of the left adrenal vein or drainage of the left adrenal vein directly into the left renal vein. 20 We found that intraprocedural left renal venogram was sufficient to identify the anatomy of the left adrenal vein and no variant anatomy was observed in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in anatomy of the left adrenal vein are rare but must be appreciated by the operator, including the left adrenal vein directly entering the IVC, the gonadal vein, or the lower moiety of a circumaortic left renal vein. [13][14][15] Gentle venography (no more than 2-3 mL) will confirm the location. If the catheter tip position is tenuous, it may be helpful to introduce a coaxial microcatheter to provide a few centimeters of additional length to stabilize the position in the vein [ Figure 2].…”
Section: Sampling Proceduresmentioning
confidence: 99%